KONSTRUKSI ISU GENDER DALAM POLITIK: STUDI KASUS PEMILIHAN UMUM 2004 - Joko Sutarso (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2011)
Construction issue of women in politics is built on the assumption of representation, which states that the number of women in representative institutions is not proportional when compared with the number of women voters. Discourse Affirmative Action is an effort to increase the number of women’s political participation in representative institutions. Although a lot of resistance or support, affirmative action is included in the Election Law 12 of 2003 failed to increase the number of legislative candidates who sit in Parliament significantly. Study of women’s issues in Election 2004 has the urgency to understand gender issues, because legislative elections are followed by direct presidential election confronts Megawati Sukarnoputri with Susilo Bambang Yudhoyono. Competition both have crystallized the issue of gender in politics, whether that support on the one hand and women who refused leaders on the other. Construction is not only built on political arguments, but also social, cultural and religious.